KOMUNIKASI INTERPERSONAL PEGAWAI PADA DINAS SOSIAL DAN TENAGA KERJA KOTA PADANG - Anisa Rahayu (Universitas Negeri Padang, 2015)
The background of this research by the writer's observation about interpersonal communication employees in social services and labor desert town that has not been as it should be . It is thought to be influenced by many factors , one of which is the interpersonal communication that needs to be nurtured and enhanced by improving the relations and cooperation between the various parties in the office . The purpose of this study was to obtain information about employees of interpersonal communication in social services and labor desert city in terms of 1 ) familiarity , 2 ) openness , 3 ) empathy , 4 ) supportive attitude , 5 ) trust.The result showed that : 1 ) familiarity is in good category ( 4.3 ) , 2 ) the disclosure is in good category ( 3.9 ) , 3 ) empathy are in the good category ( 3.7 ) , 4 ) supportive attitude on either category ( 4,1 ) . 5 ) trust in the good category ( 3,9) . Based on these results it can be concluded that interpersonal communication employee at the Department of Social and Labor of Padang are in the good category with an average score ( 4.0 ) Keyword : interpersonal communication employees